Peran Teknologi Informasi dalam Modernisasi Administrasi Publik: Raihan A. Hanasi - Raihan A. Hanasi (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2024)
This research discusses the role of information technology in the modernization of public administration. Information technology has become a major driver in increasing the efficiency and effectiveness of public services through the automation of administrative processes and e-government systems. In addition, information technology supports transparency and accountability by facilitating public access to information and public services digitally. Data-based decision making is also enhanced by information technology, enabling more accurate and evidence-based public policy. However, the implementation of information technology in public administration faces challenges such as data security, digital divide, and changes in work culture. The results of this research conclude that modernization of public administration through information technology offers great potential for improving the quality of public services and more responsive government governance. Recommendations include investments in data security, reducing the digital divide, staff training, continuous monitoring, multi-sectoral collaboration, and developing innovation to maximize the benefits of information technology in public administration.